Al-Quran Insights Regarding Hajj Practices - Sabana, Fauzi; Rizky Sabirin; Harun Al-Rasyid (Getpress Management Journals, 2023)
The implementation of the Hajj and Umrah pilgrimages is increasingly showing developments that are becoming a very interesting highlight to study in depth. The practice of Hajj is an important thing that must be considered, especially in the practical aspects carried out, the practice of Hajj also has its own characteristics which make this pilgrimage very unique and always awaited by all Muslims in every part of the world. This event can certainly be an interesting study material as learning material to see in depth the extent of the development of the Hajj and Umrah pilgrimages throughout history. On this occasion the researcher will review some material from various literature which will then be presented in narrative form. This research uses a qualitative method with a model of interpreting Al-Quran verses thematically, then by collecting journals as processed material to discuss the material. The results of this research show that there are several components in the Hajj and Umrah pilgrimages.